Making Unique Handicrafts from Shells in Lake Bird's Nest Village - Fitria Husin (Universitas Pendidikan Ganesha, 2024)
Making unique handicrafts using shells in Sarang Burung Danau Village aims to process marine waste which can be used as a creative medium for PKK mothers, increasing creativity, soft skills and an entrepreneurial spirit from an early age. This activity is focused on making unique craft items using shells as the main material, stimulating creativity and economic empowerment in the village. This initiative involves collaboration between students from various universities involved in KKN Kebangsaan 2023 activities and the local community, emphasizing the exchange of knowledge, skills and cultural experiences. The method for this service activity is to conduct a workshop which directs the training participants to practice directly making handicrafts by following the work steps. Through workshops and hands-on activities, participants explore innovative craft-making techniques while using natural resources responsibly. With this type of qualitative research, the results of this activity are a source of pride for the community, creating economic opportunities and preserving traditional skills. The products produced include pencil cases, wall hangings, mirror frames and miniature birds. The aim of this research is to encourage environmental awareness by emphasizing the sustainable use of shellfish resources. The implication of this research is that it can encourage the use of local resources, in this case shellfish, more effectively. This can help reduce pressure on the environment and promote sustainable practices in the use of natural resources.